Maintaining vascular trauma proficiency for military non-vascular surgeons - Andrew Hall; Iram Qureshi; Jacob Glaser; Kegan Brumagen (Trauma Surgery & Acute Care Open)
Background Vascular injuries in combat casualty patients are common and remain an ongoing concern. In civilian trauma centers, vascular surgeons are frequently available to treat vascular injuries. Within the military, vascular surgeons are not available at all locations where specialty expertise may be optimal. This study aims to determine if a visiting surgeon model, where a general surgeon can visit a civilian trauma center, would be practical in maintaining proficiency in vascular surgery.Methods All vascular trauma relevant cases done by any surgical service were identified during a 2-year period at Saint Louis University Hospital between October 1, 2016 and September 30, 2018. These included cases performed by trauma/general, thoracic, vascular, and orthopedic surgery. Predictions on the number of call days to experience an operative case were then calculated.Results A total of 316 vascular cases were performed during the time period. A surgeon on call for five 24-hour shifts would experience 2.1 urgent vascular cases with 95% certainty. To achieve five cases with 95% certainty, a surgeon would have to be on call for 34 24-hour shifts.Discussion A visiting surgeon model would be very difficult to maintain to acquire or maintain proficiency in vascular surgery. High-volume trauma centers, or centers with significant open vascular cases in addition to trauma, may have more reasonable time requirements, but would have to be evaluated using these methods.Level of evidence Economic and value-based evaluations, level II.